Treating war- and conflict-related nightmares in children and youth: outcomes of a school-based intervention - Schultz, Jon Håkon; Forsberg, June; Alisic, Eva; Diab, Safwat; Harb, Gerlinde (Frontiers in Sleep, 2026)
IntroductionRecurrent nightmares often severely impair the quality of life, school functioning, and daily functioning of trauma-exposed children and adolescents. However, research to date is limited for treatments focused on reducing the impact of posttraumatic nightmares among youth in conflict zones. This study aimed to investigate the outcome of the Better Learning Program 3 (BLP) as it was implemented in over 100 schools in Gaza (2012–2017).MethodsTreatment outcome was investigated in an open trial among war- and conflict-exposed students (6–17 years of age) in Gaza (N = 1093). All participants sought help with nightmares and sleep disturbance and reported recurrent traumatic nightmares on average 4.86 nights per week. The intervention was inspired by imagery rehearsal therapy and trauma-focused cognitive behavioral therapy.ResultsStudents experienced significant week-to-week reductions in reported nightmares throughout the 8-week intervention. Approximately half of the participants reported no nightmares post-treatment, and a further 47% reported a reduction in nightmare frequency. In a 10-month follow-up, 42% of a smaller sample (n = 215) maintained treatment gains and remained free of nightmares, whereas 42% maintained a reduction of nightmares to one or two per week. Students with relapse responded effectively to booster sessions offered after follow-up.DiscussionThe current study demonstrates the apparent success of this school-based treatment, showing that it is both feasible to intervene directly with students' nightmare disturbance and to significantly reduce their nightmare frequency.